Effects of Timing and Reference Frame of Feedback: Evidence from a Field Experiment - Mira Fischer; Valentin Wagner (Institute of Labor Economics (IZA), 2018)
Information about past performance has been found to sometimes improve and sometimes worsen subsequent performance. Two factors may help to explain this puzzle: which aspect of one's past performance the information refers to and when it is revealed. In a field experiment in secondary schools, students received information about their absolute rank in the last math exam (level feedback), their change in ranks between the second-last and the last math exam (change feedback), or no feedback. Feedback was given either 1-3 days (early) or immediately (late) before the final math exam of the semester. Both level feedback and change feedback significantly improve students' grades in the final exam when given early and tend to worsen them when given late. The largest effects are found for negative change feedback and are concentrated on male students, who adjust their ability beliefs downwards in response to feedback.
Keywords: I21; M54; D91; 330; timing of feedback; change and level feedback; motivation; field experiment